FLUKTUASI AIR DALAM TUMBUHAN (PLANT WATER RELATIONS) DAN STABILITAS TAMAN NASIONAL GUNUNG HALIMUN: KIANAK { CASTANOPSIS ACCUMINATATISSIMA (BL.) DC} - Naiola, B Paul; Hoesen, D Siti Hazar (BERITA BIOLOGI, 2003)
Information on the water relations of tropical plant species are less available,. This paper deals with a study of the water relations of tropical forest tree species, Kianak {Castanopsis Accuminatatissima (Bl.) DS}], a habitant of Gunung Halimun Natinal park. The purpose of this study held in October 2001, is to understand the water relation fluctuations of tropical tree species, especially those grown in a stablie ecosystem such as National Park. Parametes meansured are water potential components incluiding total water potentials. Meansurement were conducted by Pressure Chamber. The results shows that Kianak kept their average total water potentila at -0.48 MPa, while their average Â osmotic potential were held at -1.54 MPa, thus they retained their average cells/tissues turgor pressure at 1.06 MPa. Diurnal water potentials shows no significant flutuations (-0.47 MPa at 10 am,-0.48 MPa at 1 pm and -0.48 MPa at 3 pm), thus no sign of significant water stress. The value of average water potential at turgor loss pint achieved at -1.92 MPa, indicated a phenomenon of moderate drought resistance species. Based on this results, the discussion emphasize the water relations of tripical forest plants and the important of plant water relations information in the managment of National Parks and other reserved biosphere, where plants as a main components. It is suggested to enlarge such this study (incluiding seasonal fluctuations of plant water relations and covering wider forest species), under the light of Natinal park and other biosphere sities managment.